Introduction to Evolutionary Computing - Eiben, A.E.; Smith, J.E. (Springer, 2015)
This is the second edition of our 2003 book. It is primarily a book for lecturers and graduate and undergraduate students. To this group the book offers a thorough introduction to evolutionary computing (EC), descriptions of popular evolutionary algorithm (EA) variants, discussions of methodological issues and particular EC techniques. We end by presenting an outlook to evolutionary robotics and the future of EC, as it stands poised to make a major transition from evolution within computers to the evolution of things [147]. This book is also meant for those who wish to apply EC to a particular problem or within a given application area. To this group the book is valuable because it presents EC as something to be used, rather than just studied, and it contains an explicit treatment of guidelines for good experimentation. Finally, this book contains information on the state of the art in a wide range of subjects that are interesting to fellow researchers, as quick reference on subjects outside of their own specialist field of EC.